Pregnancies through oocyte donation. A mini review of pathways involved in placental dysfunction - Caradeux, Javier; Fernández, Benjamín; Ávila, Francisco; Valenzuela, Andrés; Mondión, Mauricio; Figueras, Francesc (Frontiers in Medicine, 2024)
Pregnancies resulting from assisted reproductive techniques (ART) are increasingly prevalent worldwide. While most pregnancies conceived through in-vitro fertilization (IVF) progress without complications, mounting evidence suggests that these pregnancies are at a heightened risk of adverse perinatal outcomes. Specifically, IVF pregnancies involving oocyte donation have garnered attention due to numerous reports indicating an elevated risk profile for pregnancy-related complications within this subgroup of patients. The precise mechanisms contributing to this increased risk of complications remain incompletely understood. Nonetheless, it is likely that they are mediated by an abnormal immune response at the fetal–maternal interface. Additionally, these outcomes may be influenced by baseline patient characteristics, such as the etiology of infertility, absence of corpus luteum, and variations in endometrial preparation protocols, among other factors. This review aims to succinctly summarize the most widely accepted mechanisms that potentially contribute to the onset of placental dysfunction in pregnancies conceived through oocyte donation.